Near infrared hyperspectral imaging : a rapid method for the differentiation of maize ear rot pathogens on growth media - Bezuidenhout, Cenette (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc Food Sc)--Stellenbosch University, 2018.